Integration of Biology, Mathematics and Computing in the Classroom Through the Creation and Repeated Use of Transdisciplinary Modules. Issue 3 (16th March 2022) - Ayalew, Mentewab; Hylton, Derrick; Sistrunk, Jeticia; Melton, James; Johnson, Kiandra; Voit, Eberhard
ABSTRACT: The integration of biology with mathematics and computer science mandates the training of students capable of comfortably navigating among these fields. We address this formidable pedagogical challenge with the creation of transdisciplinary modules that guide students toward solving realistic problems with methods from different disciplines. Knowledge is gradually integrated as the same topic is revisited in biology, mathematics, and computer science courses. We illustrate this process with a module on the homeostasis and dynamic regulation of red blood cell production, which was first implemented in an introductory biology course and will be revisited in the mathematics and computer science curricula.